Xanthophyll pigments dietary supplements administration and retinal health in the context of increasing life expectancy trend - Jurja, Sanda; Negreanu-Pirjol, Ticuta; Vasile, Monica; Hincu, Mihaela Mehedinti; Coviltir, Valeria; Negreanu-Pirjol, Bogdan-Stefan (Frontiers in Nutrition, 2023)
Medicine faces nowadays the trend of increasing life expectancy of human population, with the resulting increase of degenerative age related diseases prevalence, combined with the risks of less tempered sun radiations environment exposure. Under these circumstances, our work pointed out on evaluating the effect of some xanthophyll pigments dietary supplements, actually widely recommended for prevention of retinal degenerative damages and for slowing down the progression of such age related changes if they have already occurred. These dietary supplements are already well known for their total antioxidant activity, proven by photochemiluminescence method using Antioxidant Capacity in Lipid soluble-substances procedure. We recruited in our study a number of subjects with comparable ages and retinal age related degenerative abnormalities and a similar number of healthy, normal retina subjects. We evaluated the eye medical status and the retinal risk by specific methods. Then we administered to both groups of subjects similar dosages of xanthophyll pigments dietary supplements, in which the xanthophylls were differently associated with vitamins and oligo-elements. After three years duration supplementation, the subjects were reevaluated and our paper presents our conclusions on the matter, pointing on their impact on visual health.